Decolonization of Qur'anic Exegesis: A Critique of Orientalist Hegemony in Modern Qur'anic Studies - Achmat Hilmi; Muhammad Azam (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This study aims to analyze the epistemological implications of the evolution of Orientalist methodologies in Qur'anic studies and to explore the contribution of a decolonial perspective to reconstructing the paradigm of Qur'anic interpretation. Contemporary Qur'anic studies continue to be dominated by the application of historical-critical methodologies developed within the Western academic tradition, giving rise to ongoing debates regarding the place of Islamic epistemology in Qur'anic interpretation. Although previous scholarship has extensively examined Orientalism, relatively limited attention has been devoted to investigating how the structural evolution of Orientalist methodologies—from the pioneering works of Abraham Geiger and Theodor Nöldeke to the revisionist approaches of John Wansbrough and Christoph Luxenberg—has progressively transformed the epistemic foundations of contemporary Qur'anic studies. This study employs a library research method using a qualitative-conceptual approach and critical analysis. The analysis brings Edward Said's concept of strategic formation into dialogue with the principles of Islamic epistemology, namely waḥy (revelation), naql (transmitted knowledge), ʿaql (reason), and tawātur (mass transmission). The findings reveal three major shifts in Orientalist methodology. First, the focus of inquiry moved from philological comparison to historical reconstruction and subsequently to revisionist skepticism regarding the formation, transmission, and textual authenticity of the Qur'an. Second, these methodological shifts institutionalized historical criticism as the dominant criterion of scholarly legitimacy, thereby marginalizing Islamic epistemic authorities rooted in revelation, authenticated transmission, and the classical exegetical tradition. Third, this dominance has produced an epistemic asymmetry in which Islamic interpretive frameworks are frequently treated as objects of historical investigation rather than as legitimate sources of theory and methodology. This article argues that the decolonization of Qur'anic interpretation should be understood not as a rejection of historical-critical scholarship but as an epistemological reconstruction that repositions Islamic intellectual traditions as equal partners in producing theories, methods, and analytical frameworks for contemporary Qur'anic studies.